The Impact of Work-Life Balance on Turnover Intention with Burnout as An Intervening Variable in The Indonesian Quarantine Agency - Edi Sugiono; Apris Beniawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
Human resources are a crucial element in a company's success in achieving its goals and objectives. Employees, as the company’s assets, play an important role in realizing the company's vision, mission, and strategies. Therefore, employee welfare needs to be addressed to ensure optimal performance quality and reduce high turnover rates. Turnover, or employee attrition, is a serious challenge for companies, especially when the employees leaving are those with expertise, experience, and strategic positions. High turnover intention can lead to significant recruitment costs and hinder the effectiveness of the company. The main factors influencing turnover intention are work-life balance and burnout. Poor work-life balance can lead to stress, fatigue, and an imbalance between personal life and work, which contributes to burnout. Burnout itself is a form of work-related stress that causes employees to experience intense physical, emotional, and mental exhaustion, thus increasing the likelihood of them leaving the company. This study integrates work-life balance, burnout, and turnover intention into a more comprehensive analysis framework, which has not been widely explored in previous research. This research focuses on middle-level employees in Indonesia who are vulnerable to turnover due to high job demands, work stress, and lack of legal certainty regarding job identity. The research method used is quantitative with a descriptive and associative approach to analyze the relationships between these variables. The results of the study show that work-life balance does not have a significant impact on turnover intention, but plays a role in reducing burnout. Meanwhile, burnout has a direct impact on turnover intention, indicating that high levels of work fatigue contribute to employees’ decisions to leave the company.